Surfactant therapy for acute respiratory distress in infants - Corrado Moretti; Caterina S. Barbàra; Rosanna Grossi; Stefano Luciani; Fabio Midulla; Paola Papoff (Hygeia Press di Corridori Marinella, 2014)
Acute respiratory distress syndrome (ARDS) remains the primary indication for admission to paediatric intensive care units and accounts for significant mortality, morbidity and resource utilization. Respiratory infections, in particular pneumonia and severe bronchiolitis, are the most common causes of respiratory failure requiring mechanical ventilation in infants and children. This paper reviews the pathophysiology of ARDS and the management of paediatric patients with acute lung injury. Data indicate that adoption of a lung protective ventilation with low tidal volumes and of an open-lung ventilation strategy, characterized by sufficient positive end-expiratory pressure (PEEP) to avoid atelectasis, provides the greatest likelihood of survival and minimizes lung injury. The relative benefits of strategies such as high frequency oscillatory ventilation (HFOV), inhaled nitric oxide (iNO), recruiting manoeuvres and prone position are also considered. Moreover this article examines exogenous lung surfactant replacement therapy and its efficacy in the treatment of paediatric ARDS. In infants and children with acute lung injury the endogenous surfactant system is not only deficient, as observed in preterm infants, but altered via a variety of other mechanisms like inhibition and dysfunction. All factors contribute to the altered physiology seen in ARDS. The role of exogenous surfactant in lung injury beyond the neonatal period is therefore more complex and its limited efficacy may be related to a number of factors, among them inadequacy of pharmaceutical surfactants, insufficient dosing or drug delivery, poor drug distribution or, simply, an inability of the drug to counteract the underlying pathophysiology of ARDS. Several trials have found no clinical benefit from various surfactant supplementation methods in adult patients with ARDS, however some studies have shown that this therapy can improve oxygenation and decrease mortality in some specific clinical conditions of paediatric ARDS. Further studies in the paediatric field are therefore needed to clarify aspects of drug composition, dosage, dilution and timing of delivery and new researches must be carried out on development of more robust pharmaceutical surfactants.   Proceedings of the 10th International Workshop on Neonatology · Cagliari (Italy) · October 22nd-25th, 2014 · The last ten years, the next ten years in Neonatology Guest Editors: Vassilios Fanos, Michele Mussap, Gavino Faa, Apostolos Papageorgiou